Bean’s syndrome - Elguera-Falcón, Federico (2019)
An 18 year-old-man with seven days of disease duration, presented with weakness, fatigue and dizziness. At physical examination, it was found pallor and non tender and irregularnodules, bluish and different sizes on feet and hypogastrium. He had hemoglobin 2 g/dL and on endoscopy there were many deep bluish nodules with smooth surfaces in gastriccompatible with Bean’s syndrome.